Environmental design and people with visual impairments - Attaianese Erminia; De Pascale Daniele (E3S Web of Conferences)
The International Classification of Functioning, Disability and Health (ICF) tells us that every person, throughout their life, can find themselves in a situation that causes conditions of limited physical, mental, intellectual, and sensorial abilities. The ‘WHO World report on vision’, in 2019, estimates that 2.2 billion people have a visual impairment due to various conditions and situations. Since most communication is visual, this can be a source of isolation and weakness to all people with visual impairments. The built environment has been designed to be enjoyed by sighted people, but this makes it difficult for visually impaired people to use. One of the main difficulties for blind people is indeed adapting and orienting themselves in unfamiliar indoor environments. This is particularly noticeable as it is necessary to have clear guidance with the help of assistive devices in order to better understand unfamiliar spaces. There are several solutions on the open markets that allow visual impairment people to better enjoy the environment. Based on a literature review, the aim of this paper is to examine the various existing research studies that investigate how environmental design can support accessibility for people with visual impairments.